1998
DOI: 10.1098/rspb.1998.0362
|View full text |Cite
|
Sign up to set email alerts
|

New phylogenetic perspectives on the Cervidae (Artiodactyla) are provided by the mitochondrial cytochrome b gene

Abstract: The entire mitochondrial cytochrome b (cyt b) gene was compared for 11 species of the artiodactyl family Cervidae, representing all living subfamilies, i.e. the antlered Cervinae (Cervus elaphus, C. nippon, Dama dama), Muntiacinae (Muntiacus reevesi), and Odocoileinae (Odocoileus hemionus, Mazama sp., Capreolus capreolus, C. pygargus, Rangifer tarandus, Alces alces); and the antlerless Hydropotinae (Hydropotes inermis). Phylogenetic analyses using Tragulidae, Antilocapridae, Gira¤dae and Bovidae as outgroups p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
110
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 35 publications
14
110
2
1
Order By: Relevance
“…4 including morphology (Merino et al, 2005), isozymes (Smith et al, 1986), cytogenetics (Duarte and Merino, 1997), and DNA sequences (Randi et al, 1998;Randi et al, 2001;Pitra et al, 2004;Gilbert et al, 2006), a great deal of confusion still remains with regards to their evolutionary history and taxonomy. These studies resulted in conflicting hypotheses about the phylogenetic relationships within the Neotropical cervids and hence, inducing uncertain evolutionary interpretations.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…4 including morphology (Merino et al, 2005), isozymes (Smith et al, 1986), cytogenetics (Duarte and Merino, 1997), and DNA sequences (Randi et al, 1998;Randi et al, 2001;Pitra et al, 2004;Gilbert et al, 2006), a great deal of confusion still remains with regards to their evolutionary history and taxonomy. These studies resulted in conflicting hypotheses about the phylogenetic relationships within the Neotropical cervids and hence, inducing uncertain evolutionary interpretations.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The small red brocket was later recognized based on the enormous karyotypical distance (2n = 32 to 34 in M. bororo vs. 2n = 50 to 53 in M. americana of the same geographic region; Duarte and Jorge, 2003 (Randi et al, 1998(Randi et al, , 2001Pitra et al, 2004;Gilbert et al, 2006). haplotype that was obtained from GenBank did not have a species designation.…”
Section: Nemorivaga) and Red Brockets (M Americana M Nana M Boromentioning
confidence: 99%
See 1 more Smart Citation
“…Randi et al (1998) used cytochrome b (Cyb) for effective construction of the monophyly of Plesiometacarpalia. Hassanin and Douzery, (2003) have used multigene analysis for the major Plesiometacarpalia/Telemetacarpalia dichotomy, and Amato et al (2000) have used several mitochondrial genes or regions Cyb,12S and 16S ribosomal RNA [rRNA], ND4, and ND4L) to determine the monophyly of subfamily Muntiacinae, which provided strong support for the classification of Muntiacus and determined interspecific relationships.…”
Section: Introductionmentioning
confidence: 99%
“…BLAST result of CYTB sequences showed 99.7% similarities with t h a t of complete sequence of GenBank Accession AJ000028 reported from Chinese water deer (Randi et al, 1998) BLAST search result showed that water deer SRY sequences were most similar to those from Moose (Alces alces) a n d Reindeer (Rangifer tarandus) which showed about 96% homology with both, respectively. Similarity search result of SRY protein sequence of water deer showed 93.4, 92.5 and 91.3% similarities with those reported from Moose (A. alces cameloides, AY1489651, Reindeer (R. tarandus, AB247629) and Sika deer (Ceruus nippon, AB046700), respectively.…”
Section: Resultsmentioning
confidence: 88%